2022
DOI: 10.3390/jcm11154339
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Low Glycemic Index Mediterranean Diet and Combined Exercise Program on Metabolic-Associated Fatty Liver Disease: A Joint Modeling Approach

Abstract: Background: Excessive caloric intake and reduced energy expenditure are associated with the onset of metabolic-associated fatty liver disease (MAFLD). The aim of this study was to probe the benefits of a low glycemic index Mediterranean diet (LGIMD) and a combined exercise program (CEP) on MAFLD by monitoring the clinical process through anthropometric measurement, body mass index (BMI), and specific biomarkers, such as the Homeostatic Model Assessment for Insulin Resistance (HOMA-IR). Methods: The study was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…This nding is consistent with previous studies and suggests that these individuals are potential targets for future health education and behavioral interventions 8 . Currently, lifestyle interventions for MAFLD patients focus on diet and/or exercise among studies 30,31 , but the combined effect of all lifestyle behavioral interventions in MAFLD remains unclear. Considering these results, we recommend implementing interventions that promote multiple healthy lifestyles simultaneously.…”
Section: Discussionmentioning
confidence: 99%
“…This nding is consistent with previous studies and suggests that these individuals are potential targets for future health education and behavioral interventions 8 . Currently, lifestyle interventions for MAFLD patients focus on diet and/or exercise among studies 30,31 , but the combined effect of all lifestyle behavioral interventions in MAFLD remains unclear. Considering these results, we recommend implementing interventions that promote multiple healthy lifestyles simultaneously.…”
Section: Discussionmentioning
confidence: 99%
“…Blood samples and anthropometric measurements (weight, height, waist circumference) were collected by trained staff using standardized methods. More details are given in our previous study [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…The muscle-building part of the training was divided into three levels of difficulty (basic, intermediate, and advanced) [ 14 ]. The work intensity varied progressively from 65% to 75% of the 1RM.…”
Section: Methodsmentioning
confidence: 99%
“…However, Curci et al, recorded improvement in metabolic-associated fatty liver disease with a low GI Mediterranean diet and a combined exercise program for 12 months [70]. Other studies on low GI Mediterranean diet in patients with moderate or severe NAFLD also reported reduction in NAFLD scores [71] [72].…”
Section: Benefits Of Low Glycemic Index Foods: Clinical Evidencesmentioning
confidence: 99%